'The deadliest error': translation, international relations and the news media. (1st September 2016) - Zanettin, Federico
ABSTRACT: This article discusses the role of translation in the making of international politics. While being largely invisible, translation and interpreting activities are interwoven with political communication, both in contexts of direct negotiations among the parties involved and when the media act as a mediating agent by recontextualising political statements and documents across languages and cultures. This article examines two such episodes at times of diplomatic crisis and war. The first concerns the statement made by the Japanese prime minister after the Potsdam ultimatum in 1945; the second concerns remarks by the Iranian president during the conference 'A World without Zionism' in 2005. After a discussion of the linguistic features of the source and translated statements, and of their interpretation and use, it is argued that the translation strategies adopted by the media contribute to actively shape international relations, and that translation activities deserve to be attentively taken into consideration by policy and opinion makers, as well as by the general public.